The Effects of Listening to Quran Recitation on Patients Undergoing Hemodialysis: A Scoping Review - Rahmah, Tira Nur; Ibrahim, Kusman; Pratiwi, Sri Hartati (Media Publikasi Cendekia Indonesia, 2025)
Hemodialysis (HD) is part of the therapy for chronic kidney disease (CKD) patients to partially replace kidney function. However, the routine process of hemodialysis, which is performed two to three times a week, has an impact to patient’s quality of life. Spiritual-based interventions, such as listening to Quran recitation, are emerging as a complementary-therapies to address the symtomps experienced by patients undergoing hemodialysis. However, the potential use of listening to the quran in patients undergoing hemodialysis remains limited. Therefore, this study aims to explore and assess the effects of listening to Quran recitation in CKD patients undergoing hemodialysis. The scoping review was used in this study. The eligibility criteria of this study, include all full-text primary studies written in English and published between 2015 and 2024. The literature systematically searched using 3 databases, such as PubMed, Scopus, and EbscoHost with keywords